2011
DOI: 10.4236/njgc.2011.13015
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Processing of Silica Nuclear Waste Glasses

Abstract: A complex Sol-Gel process has been used for synthesis of silica glasses designed to contain high-level nuclear wastes. Cs, Sr, Co, and Nd (generically denoted Me) were used, the last as surrogate for actinides. Gels in the form of powders and sintered compacts were prepared by hydrolysis and polycondensation of tetraethoxide/Me nitrate solutions, which contained ascorbic acid as a catalyst. Thermal treatment studies were conducted on the resulting gels. Transformation to final products was studied by thermogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The porous structure of the aerogel is used as a volume host. This method would make it possible to confine nuclear waste in the porosity [19,33,34]. The important characteristic is the very high chemical durability of the silica matrix that would protect nuclear waste from corrosion by water.…”
Section: 5) Multi Component Glassesmentioning
confidence: 99%
“…The porous structure of the aerogel is used as a volume host. This method would make it possible to confine nuclear waste in the porosity [19,33,34]. The important characteristic is the very high chemical durability of the silica matrix that would protect nuclear waste from corrosion by water.…”
Section: 5) Multi Component Glassesmentioning
confidence: 99%
“…Drying may require temperatures nearer 100 °C, and additional compaction may be desirable. Sol-gel processes tend to be highly tolerant of additives; for example, incorporation of salt and oxide surrogates into durable waste forms has been demonstrated in proof-of-concept experiments [Deptula 2011, Zelinski 1998]. A significant drawback, however, is the need to collect and manage hydrolysis byproducts such as ethanol or methanol.…”
Section: Low Temperature Sol-gel Processingmentioning
confidence: 99%
“…The properties of silica glasses, including good durability and mechanical strength and the ability to incorporate large concentrations of dopants, make them ideal candidates as matrices for the storage of nuclear waste. The main disadvantage of silica glasses for this kind of use is their high processing temperature of ∼2,000 ∘ C. However, it has been shown that the sol-gel process is an appropriate low temperature process to obtain glasses at around 1,000 ∘ C, not by melting but by sintering of a nanoporous amorphous silica gel [13][14][15][16][17][18][19][20]. In this paper, we compare different nanoporous silica networks as possible host matrices for actinides and assess the feasibility of fixing actinides in silica glass.…”
Section: Introductionmentioning
confidence: 99%